An Analysis of Maqasid al-Shariah on Alternatives to the Death Penalty in Law No. 1 of 2023 Concerning the Criminal Code - Nasution, Liantha Adam; Mapaung, Watni; Harahap, Arifuddin Muda (Faculty of Law, Universitas Pekalongan, 2024)
The research was a qualitative legal study concerning alternatives to the death penalty as stipulated in Law Number 1 of 2023 on the Criminal Code, and it was evaluated from the perspective of maqashid al-shari'ah. The method involved initially collecting both primary and secondary data, which were then scrutinized within relevant literature. After examining and analyzing the data, the researcher concluded that the alternative provisions to the death penalty in Law Number 1 of 2023 on the Criminal Code exhibit both similarities and differences compared to Islamic law as interpreted by maqashid shariah. The similarities include that both the Law and Islamic law offer alternative sanctions that no longer involve taking a life, which in the context of the National Criminal Code could be considered aligned with maqashid shariah. However, a notable difference lies in cases of murder or taking another's life, where Islamic law does not allow for the alternative sanction of diyat (financial compensation) unless the victim's family forgives the perpetrator. For the National Criminal Code to align with maqashid shariah in providing an alternative to the death penalty for murder (resulting in the loss of life), it must first secure forgiveness from the victim's family as a prerequisite to commuting the sentence from death to life imprisonment or a maximum of 20 years in prison.